Thermodynamic analysis and experimental investigation of a unique photoelectrochemical hydrogen production system - Acar, Canan; Dincer, Ibrahim (PERGAMON-ELSEVIER SCIENCE LTD, 2018)
In this study, we thermodynamically analyze and experimentally investigate a continuous type hybrid photoelectrochemical H-2 generation reactor. This system enhances solar spectrum use by employing photocatalysis and PV/T. Additionally, by replacing electron donors with electrodes to drive the photocatalysis, the potential of pollutant emissions are minimized. In this study, the present reactor is tested under electrolysis operation during which the present reactor is investigated under three different inlet mass flow rates (0.25, 0.50, and 0.75 g/s) and four different operating temperatures (20, 40, 60, and 80 degrees C). Some parametric studies are run by varying the environmental temperature between 0 and 40 degrees C. In addition, the impact of coating the membrane electrode assembly of the reactor with Cu2O is investigated. The present results show that the highest energy and exergy efficiencies occur at the environmental temperature of 20 degrees C which is about 60% and 50%, respectively. The Cu2O coated membrane gives a lot higher current readings, meaning that the coating makes the membrane more conductive and increases H-2 production by permitting ions at a higher rate. (C) 2017 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Solar energy; Hydrogen production; Energy; Exergy; Efficiency; Photoelectrochemical process; P-TYPE CU2O; H-2 EVOLUTION; WATER; PHOTOCATALYST; MEMBRANE; DESIGN; Chemistry; Electrochemistry; Energy & Fuels